Insulin Resistance Adversely Affect IVF Outcomes in Lean Women Without PCOS - Wang, Haoyu; Zhang, Yu; Fang, Xuhui; Kwak-Kim, Joanne; Wu, Li (Frontiers in Endocrinology, 2021)
Objective: To investigate the effects of insulin resistance (IR) on IVF outcomes and a potential underlying mechanism in lean women without PCOS. Design: A prospective cohort study at the University Clinic. Setting: IVF center at the University setting. Patients: A total of 155 lean women (body mass index <25) without PCOS undergoing IVF cycle. Intervention: Patients were allocated to IR and non-IR groups based on HOMA-M120. Main outcome measure(s): IVF outcomes, including egg quality, the number of mature oocytes, fertilization rate, blastocyst formation rate, advanced embryo rate, and cumulative live birth rate, were investigated. Auto-immune parameters, peripheral blood immunophenotypes, thyroid hormone, homocysteine, and 25-OH-vitamin D3 (25-OH-VD3) levels were analyzed. Results: The number of mature oocytes and blastocyst formation rate were significantly lower in the IR group as compared with those of the non-IR group (p<0.05, respectively). The proportion of peripheral blood CD19+ B cells was significantly higher in the IR group than those of the non-IR group (p<0.05). Homocysteine, 25-OH-VD3, and auto-immune parameters were the same between the two groups. Conclusion: In lean non-PCOS infertile women, IR is associated with the decreased number of mature eggs and poor embryo quality in which B cell immunity may play a role.